TEACHERS’ PERCEPTIONS AND PRACTICES OF CRITICAL THINKING INSTRUCTION IN INDONESIAN SENIOR HIGH SCHOOLS: A CASE STUDY - Anggraeny, Eka; Khongput, Somruedee (TEFLIN Journal, 2022)
This study investigated how Indonesian teachers perceived and incorporated critical thinking concepts in English language classrooms. A case-study approach was set out to investigate teacher’s perceptions and practices of critical thinking in teaching English language to twelfth-grade students in Jambi Province, Indonesia. Semi-structured interviews, classroom observation, and stimulated-recall interviews were employed to collect data from six teachers in six different senior high schools. The semi-structured interview data were categorized and reported descriptively. Hennessy et al.’s (2016) Scheme for Educational Dialogue Analysis was adopted to analyze classroom observation data, and stimulated-recall interview data were analyzed as supplemental data. The findings show that teachers perceived skills, disposition, and knowledge as key attributes of critical thinking, and active learning activities were valued more than passive learning to promote students’ critical thinking. This study also reveals that all teachers employed various teaching strategies to encourage students’ critical thinking at a certain level. The findings imply that a professional development program that better equips teachers with understanding of critical thinking concepts and more teaching strategies should be urgently designed in order to produce critical global citizens.